STUDI TIMBULAN SAMPAH PERUMAHAN DAN NON PERUMAHAN DI KOTA PALEMBANG - Putri, Nyimas Septi Rika; Jimmyanto, Hendrik (CANTILEVER, 2016)
In big cities like Palembang, garbage is a source of waste from the community with a fairly abundant volume. Garbage can come from various modes of use like something that is no longer useful because it is damaged. In achieving the development or improvement of waste management system it is necessary to know the characteristics of waste generating sources include waste generation. The purpose of this study is to calculate the amount of waste generated by the housing and non-housing sector and to analyze the relationship between waste generation between housing types with correlation analysis. This research method refers to SNI 19-3964-1994 with 100 samples of housing waste and 120 samples of non housing waste that used purposive sampling. The Result of this research : in waste generation housing type of organic waste is generated by non-permanent housing, while the type of non-organic waste is generated by the type of luxury permanent housing. For non-housing waste generation waste type of organic waste is more generated by the market sector while for non-organic waste generated by the sector of shops. From the result of the weight correlation test of waste generation, it is found that non permanent and permanent waste generation has strong correlation to permanent housing waste. From the results of Anova One Way test of weight of waste generation obtained that the weight value of waste generation for semi-permanent housing did not experience a significant difference to other types of housing.